A Global Perspective on the Incidence of Monopoly Distortions - Siying Ding; Ahmad Lashkaripour; Volodymyr Lugovskyy (CESifo GmbH, 2024)
We develop a method to measure the incidence of monopolistic markup distortions in the global economy. Using semi-parametric formulas, we measure how trade modifies the deadweight loss of markups through two channels: (1) trade-induced change in markup dispersion, and (2) international rent-shifting. The latter, which has received less attention in the literature, constitutes zero-sum welfare effects similar to implicit tariffs that tilt the terms of trade in favor of countries exporting high-markup goods. To measure these effects, we estimate firm-level markups globally using demand-based and cost-based methods and compile new data on global profit ownership. Our findings reveal that trade has greatly reshaped the global incidence of monopoly distortions, reducing the deadweight loss of markups for high-income countries by 15% while increasing it by 44% among low-income nations. These asymmetric effects are primarily due to international rent-shifting and represent an 8% implicit tariff imposed by high-income countries on low-income partners. These findings are robust to accounting for global input-output linkages and fixed investment costs. Our results challenge the prevailing view that high-income countries have made disproportionately greater concessions under existing trade agreements. We show that rent-shifting externalities can be effectively mitigated through additional preferential tariff concessions under the WTO or a globally coordinated destination tax on profits.
Keywords: F12; F13; F14; O24; O25; 330; markup; incidence; distortion; market power; trade; profits; rents; welfare; unequal; tariff; policy